Multiplexed PCR assays for the detection of Shiga toxin-producing Escherichia coli, other than the top-7 serogroups, isolated from feedlot cattle feces - Porter, Bailee; Ludwig, Justin; Shi, Xiaorong; Bai, Jianfa; Nagaraja, T.G. (My University, 2017)
Purpose: Shiga toxin-producing E. coli (STEC) are major food borne pathogens. A majority of foodborne infections are associated with seven serogroups, often called top-7. The top-7 STEC include serogroups O26, O45, O103, O111, O121, O145, and O157. STEC organisms reside in the hindgut of cattle and are shed in the feces, which serve as a source of contamination of beef, produce, and water for human infections. Cattle harbor multiple other STEC serogroups (n=113), and some have been associated with human illnesses. We have developed and validated 11 sets of multiplex PCR assays to detect 113 serogroups. Our objective was to utilize the 11 sets of multiplex PCR assays to identify STEC isolates from feedlot cattle feces that did not belong to the top-7 STEC. Methods: One hundred and eighteen isolates from fecal samples that were collected from a single feedlot located in the Central U.S. in 2013 over a 12 week period. The isolates tested positive for stx1 (Shiga toxin 1), stx2 (Shiga toxin 2), both stx1 and 2, and/or eae (intimin), but negative for the serogroup-specific genes of the top-7 STEC. The 118 isolates included strains that tested positive for stx1 only (n=22), stx2 only (n=30), stx1 and stx2 (n=68) and/or eae (n=25) genes. Eleven sets of multiplex PCR assays targeting serogroup-specific genes (wzx, wzy, gnd, wbdA) of 113 serogroups were used to identify the strains. Each multiplex PCR assay included known strains of STEC as positive controls. Results and Conclusions: Of the 118 strains tested in the study, 95 (80.5%) belonged to 11 serogroups and 23 (19.5%) were unidentifiable (Table 1). The 11 identified serogroups included the following: O168 (29.7%), O109 (20.3%), O171 (9.3%), O74 (6.8%), O104 (4.2%), O2 (4.2%), O8 (2.5 %), O175 (.8%), O131 (0.8%), O160 (0.8%), and O169 (0.8%). Significance: Cattle harbor multiple STEC serogroups other than the top 7 in the hindgut. The results indicate the diversity of STEC shed in the feces including the four most predominant groups: O168 (29.7%), O109 (20.3%), O171 (9.3%) and O74 (6.8%). Similar to STEC O157 infections, STEC other than then top 7 associated illnesses can range from cases of sporadic to major outbreaks from mild watery diarrhea to life threatening complications of hemolytic uremic syndrome. Because these strains are either Shiga toxigenic (n=93), and some are enterohemorrhagic (n=25), the serogroups have the potential to cause human illness. Identifying the different serogroups, other than the top-7, allows for proper assessment of prevalence and potential risk of human illness.
Keywords: Fall 2017